Study of Children with Recurrent Pneumonia Admitted in a Tertiary Hospital - Rijal, Prashant; Lama, L; Shrestha, S; Kakshapati, P; Nayak, R (Nepal Medical College Journal, 2019)
Recurrent pneumonia usually occurs due to an underlying disorder that negatively affects local or systemic defence mechanisms. The aim of this study was to find out the prevalence and risk factors associated with recurrent pneumonia in children and to determine possible strategic plan needed for better clinical outcome. Children between 2 months to 15 years old who had a history of 2 or more episodes of pneumonia per year, or 3 or more episodes in a life time were investigated prospectively at Nepal Medical College Teaching Hospital. Out of 653 children admitted for pneumonia, 74 (11.3 %%) met the criteria for recurrent pneumonia. Among 74 children with recurrent pneumonia, underlying risk factors was demonstrated in 65 patients (87.8%). Most common underlying diseases were aspiration syndrome in 21.6% patients, congenital heart disease in 13.5% patients and bronchial asthma in 12.1% children. No predisposing illness could be demonstrated in 12.1% patients. Approximately 1 in 9 children with pneumonia in our hospital had recurrent pneumonia. Aspiration syndrome was the most common underlying illnesses for undiagnosed recurrent pneumonia in children.